2022
DOI: 10.3174/ajnr.a7603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Normal Breathing on the Movement of CSF in the Spinal Subarachnoid Space

Abstract: BACKGROUND AND PURPOSE: Forced respirations reportedly have an effect on CSF movement in the spinal canal. We studied respiratory-related CSF motion during normal respiration. MATERIALS AND METHODS:Six healthy subjects breathed at their normal rate with a visual guide to ensure an unchanging rhythm. Respiratory-gated phase-contrast MR flow images were acquired at 5 selected axial planes along the spine. At each spinal level, we computed the flow rate voxelwise in the spinal canal, together with the associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…For instance, the recent experiments of Ayansiji et al (2023) have shown that the presence of nerve roots significantly promotes tracer dispersion. The effect of trabeculae, which form a continuous weblike structure stretching across the spinal canal (Mortazavi et al 2018), can be modelled by adding a distributed Brinkman flow resistance term to the momentum equation, as done earlier (Gupta et al 2008;Tangen et al 2015;Sincomb et al 2022). Nerve roots and ligaments, on the other hand, are arranged in quasi-periodic rows aligned along the canal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the recent experiments of Ayansiji et al (2023) have shown that the presence of nerve roots significantly promotes tracer dispersion. The effect of trabeculae, which form a continuous weblike structure stretching across the spinal canal (Mortazavi et al 2018), can be modelled by adding a distributed Brinkman flow resistance term to the momentum equation, as done earlier (Gupta et al 2008;Tangen et al 2015;Sincomb et al 2022). Nerve roots and ligaments, on the other hand, are arranged in quasi-periodic rows aligned along the canal.…”
Section: Discussionmentioning
confidence: 99%
“…2019; Gutiérrez-Montes et al. 2022), thereby possibly promoting drug dispersion near the injection site. Also important is the effect of the different micro-anatomical features that populate the spinal canal, such as denticulate ligaments, nerve roots and trabeculae (Stockman 2006; Gupta et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well established that CSF displays an oscillatory motion in the subarachnoid space (SAS) surrounding the spinal cord, as indicated in figure 1(d). The oscillatory velocities, with peak values of the order of a few centimetres per second, are driven by the respiratory and cardiac cycles (Linninger et al 2016;Kelley & Thomas 2023), with the former being dominant in the lumbar region (Gutiérrez-Montes et al 2022) and the latter being dominant in the cervical region (Yildiz et al 2017(Yildiz et al , 2022, where most syrinxes are formed.…”
Section: Introductionmentioning
confidence: 99%
“…2016; Kelley & Thomas 2023), with the former being dominant in the lumbar region (Gutiérrez-Montes et al. 2022) and the latter being dominant in the cervical region (Yildiz et al. 2017, 2022), where most syrinxes are formed.…”
Section: Introductionmentioning
confidence: 99%